Wykorzystanie osadów ściekowych do rekultywacji terenów zdegradowanych na tle ustaleń planistycznych i uwarunkowań prawnych = Sewage sludge utilisation for reclamation of degraded areas against a background of the research carried out and legal conditions - Gawron, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sewage sludge show large value for soil forming and fertilisation. Analysing the sewage sludge proprieties, one should take into consideration its final farm implementation. A large content of heavy metals and biological contamination in sewage sludge is at present a major barrier for their agricultural utilisation. The pluses and minuses of its application for the reclamation of degraded and devastated soils as a consequence of both the valid legal conditions as well as the properties and character of sewage sludge produced in Poland are presented in the paper.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); osady ściekowe; rekultywacja; tereny zdegradowane; sewage sludge; reclamation area; degraded areas